Addition of Azathioprine to Corticosteroids Does Not Benefit Patients with IgA Nephropathy - Pozzi, Claudio (American Society of Nephrology, 2010)
The optimal treatment for IgA nephropathy (IgAN) remains unknown. Some patients respond to corticosteroids, suggesting that more aggressive treatment may provide additional benefit. We performed a randomized, multicenter, controlled trial to determine whether adding azathioprine to steroids improves renal outcome. We randomly assigned 207 IgAN patients with creatinine ≤2.0 mg/dl and proteinuria ≥1.0 g/d to either (1) a 3-day pulse of methylprednisolone in months 1, 3, and 5 in addition to both oral prednisone 0.5 mg/kg every other day and azathioprine 1.5 mg/kg per day for 6 months (n = 101, group 1) or (2) steroids alone on the same schedule (n = 106, group 2). The primary outcome was renal survival (time to 50% increase in plasma creatinine from baseline); secondary outcomes were changes in proteinuria over time and safety. After a median follow-up of 4.9 years, the primary endpoint occurred in 13 patients in group 1 (12.9%, 95% CI 7.5 to 20.9%) and 12 patients in group 2 (11.3%, CI 6.5 to 18.9%) (P = 0.83). Five-year cumulative renal survival was similar between groups (88 versus 89%; P = 0.83). Multivariate Cox regression analysis revealed that female gender, systolic BP, number of antihypertensive drugs, ACE inhibitor use, and proteinuria during follow-up predicted the risk of reaching the primary endpoint. Treatment significantly decreased proteinuria from 2.00 to 1.07 g/d during follow-up (P < 0.001) on average, with no difference between groups. Treatment-related adverse events were more frequent among those receiving azathioprine. In summary, adding low-dose azathioprine to corticosteroids for 6 months does not provide additional benefit to patients with IgAN and may increase the risk for adverse events.